A STUDY ON EARLY START IN ORAL INTAKE AFTER RESECTION OF COLORECTAL CANCER UNDER LAPAROTOMY - MAEDA, Toshiya; TANAKA, Ichiro; ASANUMA, Yuji; SHIGETA, Hiroshi; MOCHIZUKI, Atsushi; TAKAHASHI, Naoto; YAMAGUCHI, Kunihiko; HASHIZUME, Rintaro (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2004)
The purpose of this study was to examine the possibility of early start in oral intake after surgery for colorectal cancer under laparotomy. Subjects were 67 patients with colorectal cancer undergone elective surgery under laparotomy. They were scheduled to be removed a gastric tube on the 1st postoperative day; to start drinking in the evening of the 1st or in the morning of the 2nd postoperative day; to start liquid diet from the evening of the 2nd postoperative day; to start thin rice gruel (‘sanbugayu’) from the morning of the 3rd day; and then to thicken rice gruel to ‘gobu-gayu’ and ‘zen-gayu’ from the morning of the 4th and 5th postoperative day, respectively. As a result, 39 patients were able to follow the schedule perfectly, 14 patients were able to start oral intake after one-day behind of the removal of gastric tube; and namely, 80% of the patients were able to take usual diet orally one week after operation. It is conventionally recommended for postoperative patients with colorectal cancer to start oral intake after evacuation and defecation are confirmed and no suture failure is identified. However, we think that early start in oral intake is possible for postoperative patients with colorectal cancer under laparotomy and it may not pose problems from the standpoint of safety including complications.